Plate waste as an indicator of portion inadequacy at school lunch - Dinis, Dânia (2013)
Quality of school meals is one of the major concerns of governments and international organizations worldwide. This study aims to evaluate nutritional compliance of meals served at a Portuguese primary school considering the portions stated by Portuguese Education Ministry. To evaluate adequacy of portions served, weighing of all meal components offered to students and leftovers was performed during ten consecutive days at two different moments. Plate waste (%) was calculated by the ratio of food discarded and food served to the children. Nutritional evaluation of menus was made using the Portuguese Food Composition Table. Meals evaluated showed a percent contribution to energetic daily intake higher than recommendations. Meals served to children were considered high energy and protein dense. No significant waste of soup was accounted and the main meal components wasted were fish and vegetables. It will be necessary to adjust portions indicated by Ministry of Education in order to comply with recommendations and reduce food waste.